Comparison of Reaction Time, Accuracy, and Practice Effects Between Gamers, Semi-Gamers, and Non-Gamers. - Usgaonkar, Ugam P. S.; Braganca, Cleta F.; Shetty, Aksha (Optometry & Visual Performance, 2023)
Background: Video games are largely favoured by younger generations. Many researchers have shown the positive effect of video games on the brain and cognitive functions. This study aims to compare visual reaction time, accuracy, and practice effects between gamers, semi-gamers, and non-gamers and to investigate whether previously inexperienced participants can improve their performance with practice. METHODS: A cross-sectional study was conducted among gamers, semi-gamers, and non-gamers, in which each group comprised 15 subjects. A mobile-based reaction time application and a reaction trainer application were used to measure reaction time, score, and accuracy rate. Practice sessions were administered for all of the subjects over a period of one week, and the measurements were repeated. Paired-t test was used to compare various parameters before and after practice. Comparison between the three groups was made using a one-way ANOVA. RESULTS: Reaction time decreased significantly after practice in all groups. The semi-gamers and non-gamers, however, showed significant improvement compared to gamers. Comparing the three groups, the gamers displayed the shortest reaction time, both before (mean=251.20 msec, p=0.015) and after (mean=240.60 msec, p=0.113) practice. The accuracy rate was highest among the gamers. Gamers achieved higher scores both before (p=0.009) and after practice (p=0.001) compared to those having little or no gaming experience. CONCLUSION: Regular involvement in action video games resulted in improvement in attentional and cognitive skills in gamers, leading to better performance in reaction time, score, and accuracy rate compared to semi-gamers and non-gamers. The administration of practice over a short period of time drastically improved the performance of the non-gamers.